Marine Oil Snow, a Microbial Perspective - Gregson, Benjamin H.; McKew, Boyd A.; Holland, Robert D.; Nedwed, Timothy J.; Prince, Roger C.; McGenity, Terry J. (Frontiers in Marine Science, 2021)
Under certain conditions, dispersed crude oil in the sea combines with organisms, organic matter and minerals to form marine oil snow (MOS), thereby contributing to the sinking of oil to the seafloor. Marine microbes are the main players in MOS formation, particularly via the production of extracellular polymeric substances. Distinct groups of microbes also consume the majority of the hydrocarbons during descent, leading to enrichment of the less bioavailable hydrocarbons and asphaltenes in the residue. Here we discuss the dynamics of microbial communities in MOS together with their impacts on MOS evolution. We explore the effects of dispersant application on MOS formation, and consider ways in which laboratory experiments investigating MOS formation can be more representative of the situation in the marine environment, which in turn will improve our understanding of the contribution of MOS to the fate of spilled oil.